Comparing Performance Using Balance Scorecard Method: Evidence of Conventional vs Shariah Insurance Firms - Trie Nadirra; Fazli Syam BZ; Muslim A. Djalil (Universitas Syiah Kuala, 2020)
Objective – The purpose of this study is to evaluate and compare the overall company performance using the concept of Balance Scorecard at conventional insurance firm and its Syariah counterpart. This study took the case of an insurance company which have its conventional as well as Syariah branch namely PT AB Medan Branch and PT AB Syariah Aceh Branch. Design/methodology – Sample in this study were employees and partners both from PT AB Medan Branch and PT AB Syariah Aceh Branch. Secondary data were derived from financial statements for 2 years period of 2018-2019. Results – The results of the study showed that (1) when viewed from a financial perspective, PT AB Medan Branch is better than PT AB Aceh Branch; (2) when viewed from a non-financial perspective (customer satisfaction and learning growth), both PT AB Medan Branch and PT AB Syariah Aceh Branch show very good signs of satisfaction, namely the average value above 4; and (3) when viewed from a non-financial perspective (internal business processes) PT AB Medan Branch is better than PT AB Aceh Branch. This implies the different strength portrayed by conventional and shariah insurance firms indicating the areas that they can focus for improvement.